2020
DOI: 10.1093/burnst/tkaa027
|View full text |Cite
|
Sign up to set email alerts
|

Burns in the elderly: a nationwide study on management and clinical outcomes

Abstract: Background In modern-day burn care, advanced age remains an important predictor for mortality among burn victims. In this study, we compared the complete treatment trajectory (including pre-hospital and surgical treatment) and the outcomes between an elderly burn population and a younger adult burn population. Methods In this nationwide study, data from the Dutch Burn Repository were used. This is a uniform national registrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
3
20
0
4
Order By: Relevance
“…At present, the reported proportion of elderly burns in China has increased from 3.4% [ 9 ] (patients admitted from 1999 to 2004) or 3.8% [ 7 ] (patients admitted from 2003 to 2009) in the early stage, to 7.5% [5] (patients admitted from 2010 to 2016) in the recent stage. This study showed that the proportion of elderly burns has increased from 5.7% in 2004 to 8.6% in 2018, which was generally consistent with previous reports, but lower than that in developed countries such as the Netherlands [ 10 ] (10.0%, patients admitted from 2009 to 2015), the United States [ 11 ] (10.1%, patients discharged from 1997 to 2010). This may be related to the lack of medical resources and ability to pay for medical expenses in China, leading to more elderly burns being treated in outpatient clinics or even at home.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At present, the reported proportion of elderly burns in China has increased from 3.4% [ 9 ] (patients admitted from 1999 to 2004) or 3.8% [ 7 ] (patients admitted from 2003 to 2009) in the early stage, to 7.5% [5] (patients admitted from 2010 to 2016) in the recent stage. This study showed that the proportion of elderly burns has increased from 5.7% in 2004 to 8.6% in 2018, which was generally consistent with previous reports, but lower than that in developed countries such as the Netherlands [ 10 ] (10.0%, patients admitted from 2009 to 2015), the United States [ 11 ] (10.1%, patients discharged from 1997 to 2010). This may be related to the lack of medical resources and ability to pay for medical expenses in China, leading to more elderly burns being treated in outpatient clinics or even at home.…”
Section: Discussionsupporting
confidence: 91%
“…The treatment of elderly burns involves many problems such as medical aid system and social ethics [6,10]. In this study, 34 patients (1.3%) gave up treatment by themselves or their families.…”
Section: Discussionmentioning
confidence: 93%
“… 7 , 28–30 Our data showed that in colistin-treated patients the overall mortality rate of 37.6% (50/133 patients) was related to older age, a higher percentage of third-degree burn areas, and severity of AKI, all well-known risk factors for death in the general burn population. 31 , 32 In the same way, by comparing colistin- and other antibiotic-treated groups, we found that a higher mortality rate and the severity of the burn were more frequently associated with MDRGN strains such as Acinetobacter baumannii , Pseudomonas aeruginosa and Klebsiella pneumoniae maintaining colistin as a unique sensitivity to antibiotics. In effect, the patients of the control group presented different types of MDRGN strains, and they were also treated with the new antibiotics specifically active against MDRGN when appropriate.…”
Section: Discussionmentioning
confidence: 59%
“…Older people are at high risk of burn injuries and related adverse outcomes due to cognitive impairment, low immunity, slow wound healing, and decreased mobility [ 4 , 5 ]. Moreover, painful diseases including osteoarthritis, diabetic neuropathy and lower back pain make older people more vulnerable to the negative consequences of burn injuries compared with younger adults [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%